Latihan Fisik Pada Kelompok Lansia Di Puskesmas Mulyoharjo Pemalang - Nunung Hasanah; Siwi Sri Widhowati; Santoso Tri Nugroho; Ade Irma Nahdliyah; Dhimas Khairil Ikbal; Noor Ariefah Tis'ah Baniyati (Calory Journal Medical Laboratory Journal, 2023)
The process of growing old is a phase in a person's life cycle with characteristics found to decrease every function of body organs, such as physical, emotional, psychological conditions and social abilities. Decreased physical function that also occurs in the musculoskeletal system is calcification and decreased production of synovial fluid in the joints. This is the cause of the elderly lazy to move because of pain and stiffness. Lack of movement will cause other health problems such as atrophy or contacture in the muscles. Lack of physical activity and sedentary behavior, resulting in decreased physical fitness and subsequent impact on physical health, well-being, sleep patterns and quality of life. In the elderly, physical fitness can be maintained with regular physical exercise from an early age, and carrying out a healthy lifestyle. Physical exercise refers more to planned, structured, and repetitive physical activity to improve or maintain body fitness. Older or elderly people are advised to take advantage of physical exercise. Some physical exercises that can be taught to the elderly. Activities in this community service are blood pressure measurement and physical exercise in the form of elderly gymnastics, which is carried out at the Mulyoharjo Health Center by involving professional students. When gymnastics, the elderly seem enthusiastic and can participate in activities and look fit.